Efficiency of the actions of the State to combat the evasion of contributions to the General System of Social Security (2017)
Given that there is a significant number of independents in Colombia, this essay analyzes the actions that the State has taken to combat the contribution ́s evasion to the General System of Social Security in Health SGSSH. It identifies that there is an entity: The Special Administrative Unit of Pension Management and Contributions of the Social Protection - UGPP -, which is responsible for the majority of actions against evasion; the actions are: treatment persuasive, control, training and sanctions. The results of the analysis will allow an evaluation of the actions that have been implemented have been sufficient.